Aeroacoustic Noise Source Identification Using Irregularly Sampled LDV Measurements Coupled with Beamforming (AIAA-2011-2719) - Bennett, Gareth (My University, 2011)
This paper develops a technique which relates dynamic pressure measurements taken outside the hydrodynamic eld of a low speed jet to single point, one component velocity measurements taken within the jet using a Laser Doppler Velocimetry (LDV) system. To improve the signal to noise ratio of the pressure measurement, a coherence based acoustic beamforming technique is applied and focussed on the LDV measurement volume in order to evaluate its contribution to the measured sound. As the pressure samples are acquired at regular time steps whereas the velocity at irregular time intervals dependent on the particle seeding, the calculation of the auto- and cross-spectra of the pressure and veloc- ity measurements require special treatment. The signal processing procedures required to calculate these are described and implemented in the paper. To validate the proposed tech- nique real experimental data was analysed. Laser Doppler Velocimetry measured velocity uctuations created by rods placed in a jet. Synchronously, a planar random array focused on the same plane as the LDV measurement, measured pressure uctuation outside the hydrodynamic eld. The same set of data was then analysed using conventional and co- herence based beamforming algorithms. The results from both techniques were compared. While conventional beamforming identi ed the contribution from the main sources within the ow, the coherence based method was able to single out the source related to the local measurement. The results shown demonstrated how coherence based beamforming, combined with LDV, can be a useful tool for aeroacoustic noise source investigations.
17th AIAA/CEAS Aeroacoustics Conference (32nd AIAA Aeroacoustics Conference)
PUBLISHED
Portland, Oregon, USA
Keywords: Aeroacoustics; Beamforming; Noise Source Identification; Coherence; Laser Doppler Anenometry (LDA); Jet Noise; Sample and Hold; Rod Noise; Vortex Shedding; Strouhal; Smart & Sustainable Planet